EKSTRAK KULIT BUAH NAGA TERHADAP RENDEMEN DAN ORGANOLEPTIK VCO SEBAGAI BAHAN AJAR BERUPA LKPD - Ayu Vitania Haryanto; HRA Mulyani; Handoko Santoso (EDUBIOLOCK, 2025)
The aims of this research are; to determine the effect of the concentration of red dragon fruit peel extract on the results of the yield and organoleptic tests, to determine the best concentration on the results of the yield and organoleptic tests and for the preparation of teaching materials (LKPD) on biotechnology materials. The organoleptic test aims to determine the level of preference for VCO based on 3 parameters namely: 1) Color, 2) Taste, 3) Texture This research is an experimental research with a RAL research design with 5 treatments (P1; 15%, P2; 20%, P3; 25%, P4; 30%, P5; 35%) and 6 replications. The data analysis technique in this research uses ANOVA 1. Based on the analysis results; The concentration of dragon fruit peel extract influences the yield results and organoleptic tests. The P1 concentration produced the highest yield and the best organoleptic tests on 3 parameters (color, taste, texture). The source of teaching materials (LKPD) for biotechnology material has been validated by design experts and material experts, with a design aspect percentage of 95.27% and a material aspect percentage of 98.43% with the category very valid and suitable for use.